Variation in percentage-free prostate-specific antigen (PSA) with prostate volume, age and total PSA level. - Törnblom, M; Norming, U; Becker, C; Lilja, H; Gustafsson, O (2001)
OBJECTIVE: To examine the correlation between prostate volume, patient age and total prostate-specific antigen (tPSA) with the percentage-free PSA (f/tPSA) in a population-based cohort of men with no prostate cancer and with a tPSA of < 10.0 ng/mL. SUBJECTS AND METHODS: Men who in 1988-1989, after randomized selection in the general population, participated in a population-based screening study for prostate cancer, were investigated. In all, 1622 of the men (aged 55-70 years) were considered free from prostate cancer and had a tPSA level of < 10.0 ng/mL. The f/tPSA and tPSA were determined in frozen sera from each individual, and related to prostate volume and age measured at the time of the study. The entire population was investigated, as were four subpopulations based on tPSA levels (< 2.0, 2.0-3.9, 4.0-6.9 and 7.0-9.9 ng/mL). Statistical calculations included multiple regression and correlation analysis. RESULTS: The f/tPSA level varied with prostate volume and age, but the decisive factor for this variation was the tPSA level. The closest correlation was in the tPSA interval 7.0-9.9 ng/mL, where volume and age together explained 47% of the variation in f/tPSA. Also, for men with tPSA levels in each of the intervals 2.0-3.9, 4.0-6.9 and 7.0-9.9 ng/mL, the f/tPSA increased with higher prostate volumes and age. In men with tPSA levels of < 2.0 ng/mL the f/tPSA was not affected by variations in prostate volume or age. CONCLUSION: The variation in f/tPSA with prostate volume, age and tPSA is highly dependent on the tPSA level. Volume and age in the tPSA interval 7.0-9.9 ng/mL can explain almost half the variation in f/tPSA, whereas this influence is insignificant in men with a tPSA of < 2.0 ng/mL.